2011
DOI: 10.1099/mic.0.044941-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of type III secretion system (T3SS)-1-independent entry mechanisms used by Salmonella Enteritidis to invade different cell types

Abstract: Salmonella causes a wide range of diseases from acute gastroenteritis to systemic typhoid fever, depending on the host. To invade non-phagocytic cells, Salmonella has developed different mechanisms. The main invasion system requires a type III secretion system (T3SS) known as T3SS-1, which promotes a Trigger entry mechanism. However, other invasion factors have recently been described in Salmonella, including Rck and PagN, which were not expressed under our bacterial culture conditions. Based on these observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 27 publications
(38 reference statements)
3
44
1
Order By: Relevance
“…In vivo studies with S. Dublin and S. Typhimurium serotypes have demonstrated that the T3SS-1 is essential for intestinal colonization and is required to induce enterocolitis in bovine, rabbit and murine models (Wallis & Galyov, 2000). In contrast, recent studies demonstrate that different serotypes of Salmonella lacking T3SS-1 still have the ability to invade in vitro cells of diverse origins and can be pathogenic in different in vivo infection models (Aiastui et al, 2010;Rosselin et al, 2011). In addition, it was shown that the T3SS-1 is not required for Salmonella internalization into a 3-Dimensional intestinal epithelium (Radtke et al, 2010).…”
Section: T3ss-1 Contribution To Salmonella Pathogenesismentioning
confidence: 97%
See 4 more Smart Citations
“…In vivo studies with S. Dublin and S. Typhimurium serotypes have demonstrated that the T3SS-1 is essential for intestinal colonization and is required to induce enterocolitis in bovine, rabbit and murine models (Wallis & Galyov, 2000). In contrast, recent studies demonstrate that different serotypes of Salmonella lacking T3SS-1 still have the ability to invade in vitro cells of diverse origins and can be pathogenic in different in vivo infection models (Aiastui et al, 2010;Rosselin et al, 2011). In addition, it was shown that the T3SS-1 is not required for Salmonella internalization into a 3-Dimensional intestinal epithelium (Radtke et al, 2010).…”
Section: T3ss-1 Contribution To Salmonella Pathogenesismentioning
confidence: 97%
“…A Salmonella mutant, unable to express its T3SS-1 is still able to invade numerous cell lines and cell types and is shown to induce both intense and local membrane rearrangements (Rosselin et al, 2011). However, to date, little is known about the entry factors mediating these T3SS-1 independent invasion mechanisms.…”
Section: Invasion Mechanisms Independent Of the T3ss-1mentioning
confidence: 99%
See 3 more Smart Citations